2011
DOI: 10.1007/s11695-011-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) on Weight Loss and Biomarker Parameters in Morbidly Obese Patients: A 12-Month Follow-Up

Abstract: LRYGB appears to be a safe and effective procedure with a low complication rate in Iranian morbidly obese patients. It results in weight loss, reduction in obesity comorbidities, increasing HDL, and decreasing other measured plasma biochemical parameters. Based on our results, we suggest that LRYGB would benefit young male morbidly obese patients more than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This is concerning, as higher ALP concentrations are seen in Alzheimer's disease patients and correlated with the neurotoxic effects of tau protein (Vardy et al, 2012; Diaz-Hernandez et al, 2010). Fortunately, ALP concentrations have been shown to improve following bariatric surgery (Toolabi et al, 2011). Yet, the literature is not entirely consistent on this matter, as extant evidence also shows no changes in ALP concentrations after bariatric surgery (De Abreu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concerning, as higher ALP concentrations are seen in Alzheimer's disease patients and correlated with the neurotoxic effects of tau protein (Vardy et al, 2012; Diaz-Hernandez et al, 2010). Fortunately, ALP concentrations have been shown to improve following bariatric surgery (Toolabi et al, 2011). Yet, the literature is not entirely consistent on this matter, as extant evidence also shows no changes in ALP concentrations after bariatric surgery (De Abreu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Past work shows that bariatric surgery can improve cystatin C and ALP concentrations (Toolabi et al, 2011; Fenske et al, 2013), though no study has examined whether this pattern of metabolic improvements is also associated with post-bariatric surgery cognitive benefits. The current study examined whether changes in cystatin C and ALP correspond to improved cognitive function following bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The current findings, in the context of past work showing that liver function often improves following bariatric surgery (19) and preoperative ALP is linked to better postoperative cognition (9), suggest a need for future work to determine the extent to which liver function directly affects cognitive abilities. Limitations of the current work include the crosssectional design and single, early postoperative time point, as well as lack of a control group comparison.…”
Section: Discussionmentioning
confidence: 63%
“…Toolabi et al showed significant improvement in all components of lipid profile one year after surgery (20). Golpaie et al reported significant reduction in LDL and triglycerides levels six weeks post-surgery (21).…”
Section: Discussionmentioning
confidence: 99%